2021
DOI: 10.48550/arxiv.2110.10121
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Approximately Dual p-Approximate Schauder Frames

Abstract: Difficulty in the construction of dual frames for a given Hilbert space led to the introduction of approximately dual frames in Hilbert spaces by Christensen and Laugesen. It becomes even more difficult in Banach spaces to construct duals. For this purpose, we introduce approximately dual frames for a class of approximate Schauder frames for Banach spaces and develop basic theory. Approximate duals for this subclass is completely characterized and its perturbation is also studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In [29], it is also showed by Christensen and Laugesen that by perturbing frame we can get approximate duals. In [61], it is showed that this result is valid for Banach spaces. Here is the operator-valued version of that result.…”
Section: Approximate Dualitymentioning
confidence: 87%
See 2 more Smart Citations
“…In [29], it is also showed by Christensen and Laugesen that by perturbing frame we can get approximate duals. In [61], it is showed that this result is valid for Banach spaces. Here is the operator-valued version of that result.…”
Section: Approximate Dualitymentioning
confidence: 87%
“…In [29], Christensen and Laugesen gave a method to construct approximately duals iteratively. In [61], this result was derived for Banach spaces. Here we have a similar result for operator-valued p-ABSs.…”
Section: Approximate Dualitymentioning
confidence: 98%
See 1 more Smart Citation
“…Definition 2.1. [82,84] Let p ∈ [1, ∞). Let {τ n } n be a sequence in a Banach space X and {f n } n be a sequence in X * (dual of X ).…”
Section: Introductionmentioning
confidence: 99%